Halophilic adaptation of protein–DNA interactions. (1st June 2003) - Bergqvist, S.; Williams, M.A.; O'Brien, R.; Ladbury, J.E.
Abstract : Pyrococcus woesei ( Pw ) is an archaeal organism adapted to living in conditions of elevated salt and temperature. Thermodynamic data reveal that the interaction between the TATA-box-binding protein (TBP) from this organism and DNA has an entirely different character to the same interaction in mesophilic counterparts. In the case of the Pw TBP, the affinity of its interaction with DNA increases with increasing salt concentration. The opposite effect is observed in all known mesophilic protein–DNA interactions. The halophilic behaviour can be attributed to sequestration of cations into the protein–DNA complex. By mutating residues in the Pw TBP DNA-binding site, potential sites of cation interaction can be removed. These mutations have a significant effect on the binding characteristics, and the halophilic nature of the Pw TBP–DNA interaction can be reversed, and made to resemble that of a mesophile, in just three mutations. The genes of functionally homologous proteins in organisms existing in different environments show that adaptation is most often accompanied by mutation of an existing protein. However, the importance of any individual residue to a phenotypic characteristic is usually difficult to assess amongst the multitude of changes that occur over evolutionary time. Since the halophilic nature of this protein can be attributed to only three mutations, this reveals that the important phenotype of halophilicity could be rapidly acquired in evolutionary time.